Safety and Efficacy of Ephedrine Alkaloids-Free Ephedra Herb Extract (EFE) for Mild COVID-19: A Double-Blind, Placebo-Controlled, Randomized Comparative Trial - Hiroshi Odaguchi; Sumiko Hyuga; Mariko Sekine; Hirofumi Michimae; Masashi Hyuga; Nahoko Uchiyama; Masashi Uema; Yuji Kumagai; Yusuke Suzuki; Shigeki Nabeshima; Norio Omagari; Yohei Doi; et al. (Microorganisms)
Several Ephedra Herb-containing Kampo medicines are common initial treatments for various infections; however, the ephedrine alkaloids in Ephedra Herb can cause side effects by stimulating adrenergic receptors. Accordingly, an ephedrine alkaloids-free Ephedra Herb Extract (EFE) has been developed. This study aimed to evaluate whether EFE can be used effectively and safely in patients with mild coronavirus disease 2019 (COVID-19). We randomized patients with mild COVID-19 to receive EFE equivalent to 6 g of Ephedra Herb per day or a placebo for 14 days. The primary efficacy endpoint was the non-aggravation rate up to Day 15. We allocated 41 and 40 patients to the EFE and placebo groups, respectively. All participants were included in the mITT and safety analysis populations [male ratio, mean age: 31.7%, 42.0 years (EFE); 17.5%, 43.2 years (placebo)]. The non-aggravation rate up to Day 15 for the primary endpoint was 100.0% and 94.6% in the EFE and placebo group, respectively, with no between-group difference. The number of days to the improvement in nausea symptoms was significantly shorter in the EFE group. One patient in the placebo group discontinued the trial due to a side effect. Although EFE demonstrated safety in patients with mild COVID-19, it did not show superior efficacy compared to placebo for symptoms other than nausea.